Enhanced corrosion resistance of Ni-W alloy with inclusion of TiN nanoparticles by electrodeposition method. (1st July 2013) - Arunsunai Kumar, K; Paruthimal Kalaignan, G; Muralidharan, V S
Abstract : Electrodeposition of Ni-W-TiN nanocomposite on mild steel substrate from an ammoniacal citrate bath containing dispersed titanium nitride has been demonstrated. The structure, surface morphology, composition and corrosion resistance properties of the nanocomposite deposits have been characterised by using various techniques. X-ray diffraction analysis (XRD) of the electrodeposited Ni-W-TiN nanocomposite shows that it is fcc crystalline. Scanning electron micrography (SEM) reveals smaller grains and uniform distribution of the titanium nitride in the alloy matrix. The microhardness of the nanocomposite coatings is higher than that of the alloy. The corrosion resistance of the electrodeposited nanocomposite evaluated by electrochemical impedance and Tafel polarization studies showed that the Ni-W-TiN nanocomposite is more corrosion resistant than the Ni-W alloy deposit. The finer grain and uniform distribution of the titanium nitride in alloy matrix favour the enhanced microhardness and corrosion resistance of the nanocomposite.